Solar Panel Tracking Control Monitoring System - Benriwati Maharmi; Johan Bagus Purnomo Sidi; Machdalena Machdalena (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
Solar energy is extraordinary and the largest energy on earth and no pollution. Solar cell technology is a technology that can absorb solar energy and convert in to electrical energy. In general, the installation of solar panels is only in one direction so that the absorption by the photovoltaic collector will not be optimal. Subsequence, the electricity produced is also less than optimal. To optimize the absorption of sunlight, the photovoltaic collector must be parallel to the sun. In this study, 4 LDR light sensors were used as detectors of the highest intensity of sunlight, the LDR output would enter the Arduino Mega microprocessor and control the DC motor to drive the solar panels. The monitoring process used a current/voltage sensor (INA219), temperature and humidity sensor (DHT 11), data from the sensor was processed by the ESP8266 Node MCU and then the data can be accessed via an Android Smartphone using the Blynk application. These data were transmitted to users wirelessly via the ESP8266 Node MCU module. From the test results, the energy generated when the solar cell was stationary averages V = 14.28 volts, I = 0.66 A and the energy when the solar cell moved averages V = 14.63 volts, I = 0.92 A. Therefore, the comparison of electric power in the condition that the solar panels moved according to the movement of the sun has increased by 30.13% compared to the stationary condition.